Technology and costs in international competitiveness: from countries and sectors to firms - Giovanni Dosi; Marco Grazzi; Daniele Moschella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper examines the determinants of international competitiveness at the level of sectors and firms. First, we address the relation between cost-related and technological competition in a sample of fifteen OECD countries. Results suggest that the countries' sectoral market shares are indeed mainly shaped by technological factors (proxied by investment intensity and patents) while cost advantages/disadvantages do not seem to play any significant role. Next, we attempt to identify the underlying dynamics at the firm level. We do that for a single country, Italy, using a large panel of Italian firms, over nearly two decades. Results show that also at micro level in most sectors investments and patents correlate positively both with the probability of being an exporter and with the capacity to acquire and to increase export market shares. The evidence on costs is more mixed. A simple measure like total labour compensation is positively correlated with the probability of being an exporter, while unit labour costs show a negative correlation only in some manufacturing sectors.
Keywords: D22; F10; F14; F19; L25; O32; 330